2014
DOI: 10.1016/j.hbrcj.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Partial strengthening of R.C square columns using CFRP

Abstract: In some buildings, when quality control is poor, the upper parts of columns have a weak compressive strength, especially in floor zone. Low compressive strength for upper part of the column will lead to a reduction in bearing capacity of column. Strengthening of this part using traditional methods such as R.C jackets and steel jackets will not satisfy the architectural conditions. Also the Egyptian code for design and construction of fiber reinforced polymers prevents partial strengthening of rectangular colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Limestone powder (LSP) was used as a filler material for the concrete mix as selfcompacting concrete with fineness 315 m 2 /kg that is classified as fine aggregate gradation zone (2). Tables 5 and 6 list the physical and chemical composition of LSP.…”
Section: Limestone Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Limestone powder (LSP) was used as a filler material for the concrete mix as selfcompacting concrete with fineness 315 m 2 /kg that is classified as fine aggregate gradation zone (2). Tables 5 and 6 list the physical and chemical composition of LSP.…”
Section: Limestone Powdermentioning
confidence: 99%
“…Many researchers investigated the concrete mechanical properties that are mixed with steel fiber and explored a different structural member with and without wrapped by FRP family. Abdel-Hay [2], investigated the behavior and strength of reinforced concrete columns strengthened by CFRP. Then, test results showed that the ultimate load of the wrapped column increases due to the confinement.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research results of previous researchers for partially FRP-confined RC columns, the strength and ductility of partially FRP-confined RC specimens can be significantly increased [ 11 , 12 , 13 ]. Barros and Ferreira [ 11 ] studied the effectiveness of the discrete confinement through concrete cylinders confined by distinct arrangements of strips of CFRP sheet under concentric load up to the failure point.…”
Section: Introductionmentioning
confidence: 99%
“…From the evaluation on the influence of the width of the strip, distance between strips, number of CFRP layers per strip, CFRP stiffness, and concrete strength class, it was found that load carrying capacity and ductility of concrete specimens increase up to 3.27 and 5.02 times, respectively. Abdel-Hay [ 12 ] investigated the overall behavior of ten RC square columns. The main parameters studied in this research were the compressive strength of the upper part, the height of the upper poor concrete part, and the height of CFRP wrapped part of column under eccentric load.…”
Section: Introductionmentioning
confidence: 99%
“…Confining of concrete elements using wrapping FRP sheets is considered as a very efficient technique to enhance both load carrying capacity and structural ductility of RC columns subjected to axial compression load [1][2][3][4][5][6]. Also, the efficiency of the wrapped FRP sheets in terms of structural performance and ease of application has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%